2018
DOI: 10.1007/s10840-018-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic comparison of different multisites and multipoint pacing strategies in cardiac resynchronization therapies

Abstract: PurposeIn order to increase the responder rate to CRT, stimulation of the left ventricular (LV) from multiple sites has been suggested as a promising alternative to standard biventricular pacing (BIV). The aim of the study was to compare, in a group of candidates for CRT, the effects of different pacing configurations—BIV, triple ventricular (TRIV) by means of two LV leads, multipoint (MPP), and multipoint plus a second LV lead (MPP + TRIV) pacing—on both hemodynamics and QRS duration.MethodsFifteen patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…A considerable effect was seen when MPP was compared to "poorer" LV sites, but the benefit was small when MPP was compared to the BiVP configuration, which yielded the largest AHR. 8,9 These findings are in line with previous work from our group in a nonischemic canine LBBB model 15 and from Bordachar et al 18 in a canine model of chronic ischemic heart failure. Even increasing the number of LV pacing sites to 6 resulted in a better AHR only if AHR during BiVP was poor.…”
Section: Hemodynamic Consequences Of LV Multisite Pacing Strategiessupporting
confidence: 89%
See 2 more Smart Citations
“…A considerable effect was seen when MPP was compared to "poorer" LV sites, but the benefit was small when MPP was compared to the BiVP configuration, which yielded the largest AHR. 8,9 These findings are in line with previous work from our group in a nonischemic canine LBBB model 15 and from Bordachar et al 18 in a canine model of chronic ischemic heart failure. Even increasing the number of LV pacing sites to 6 resulted in a better AHR only if AHR during BiVP was poor.…”
Section: Hemodynamic Consequences Of LV Multisite Pacing Strategiessupporting
confidence: 89%
“…9 In that clinical study, no difference in AHR was found between MPP and multivein pacing, although patients with ischemic cardiomyopathy were included. 9 The present study was performed in a nonischemic, acute (nonmyopathic) LBBB model. Because different studies have shown conflicting results as to whether multiple LV pacing has a greater benefit in ischemic compared to nonischemic cardiomyopathy patients, 17,24 we opted for a nonischemic model.…”
Section: Study Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…It seems that fusion and LV pre-excitation, inevitably linked to CRT, contribute independently to a rise in LV dP/dt max and a change in QRSd. 7 15 It is essential to understand the measurements’ respective value as biomarkers if one would use them for acute prediction of long-term response during CRT implantation. 5 6 18 20 This study was designed to provide knowledge on how different fusion strategies and LV pre-excitation/post-excitation determine QRSd and LV dP/dt max to provide information on the two’s potential utility as biomarkers for the prediction of long-term response to CRT.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 Research groups have therefore used LV dP/dt max and QRSd to guide different approaches to improve CRT, 4–10 including fusion of intrinsic conduction with paced wavefronts and LV pre-excitation. 7 9 11–14 The objective of this study was to analyse how fusion determines LV dP/dt max and QRSd to understand better how these measurements reflect resynchronisation and should be interpreted if they were to be used for acute haemodynamic assessment or for the prediction of long-term response from CRT. We applied biventricular stimulation with different fusion strategies, including fusion with intrinsic right ventricle (RV) activation, different degrees of fusion within the LV by LV pre-excitation/post-excitation and fusion from the LV activation site with single-point and multipoint pacing (MPP) in order to analyse the effect of different fusion strategies on LV dP/dt max and QRSd.…”
Section: Introductionmentioning
confidence: 99%